2017
DOI: 10.3390/antiox6030047
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of TXNIP Mitigates High-Fat Diet-Impaired Angiogenesis and Prevents Inflammation in a Mouse Model of Critical Limb Ischemia

Abstract: Background: Previous work demonstrated that high-fat diet (HFD) triggered thioredoxin-interacting protein (TXNIP) and that silencing TXNIP prevents diabetes-impaired vascular recovery. Here, we examine the impact of genetic deletion of TXNIP on HFD-impaired vascular recovery using hind limb ischemia model. Methods: Wild type mice (WT, C57Bl/6) and TXNIP knockout mice (TKO) were fed either normal chow diet (WT-ND and TKO-ND) or 60% high-fat diet (WT-HFD and TKO-HFD). After four weeks of HFD, unilateral hind lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Increased expression of TXNIP and reduced Trx activity have been observed in animal models of diabetes. TXNIP is a key factor in the regulation of functional β-cell mass, and inhibition of TXNIP ameliorates the symptoms of diabetes ( 40 ); for example, knockdown of TXNIP ameliorated high-glucose-induced epithelial—to—mesenchymal transition in renal tubular epithelial cells ( 60 ) and deletion of TXNIP prevented high-fat-diet-induced inflammation in critical-limb ischemic mice ( 61 ). In addition, the diabetic lipid environment can induce TXNIP expression, which stimulates the vascular inflammation ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of TXNIP and reduced Trx activity have been observed in animal models of diabetes. TXNIP is a key factor in the regulation of functional β-cell mass, and inhibition of TXNIP ameliorates the symptoms of diabetes ( 40 ); for example, knockdown of TXNIP ameliorated high-glucose-induced epithelial—to—mesenchymal transition in renal tubular epithelial cells ( 60 ) and deletion of TXNIP prevented high-fat-diet-induced inflammation in critical-limb ischemic mice ( 61 ). In addition, the diabetic lipid environment can induce TXNIP expression, which stimulates the vascular inflammation ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP deficiency impaired the activation of the NLRP3 inflammasome and the subsequent secretion of interleukin-1β (IL-1β) in macrophages. Although TXNIP-NLRP3 inflammasome axis is independent with known NLRP3 activation by oligomers of islet amyloid polypeptides (IAPP) [ 49 ] (a protein that forms amyloid deposits that has been observed during type-2 diabetes in pancreatic β cells), TXNIP-NLRP3 inflammasome axis seems to be an important regulator for specific tissue inflammation in redox dependent and independent manners [ 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Txnip/tbp-2 In Whole-body Glucose–lipid Metabolic Regulatmentioning
confidence: 99%
“…Isolated PBMCs from WT-HFD mice but not TKO-HFD mice resulted in increased leukostasis and apoptosis (p = 0.07 compared with WT-ND) of mouse retinal EC cultures, after 2 and 24 h in co-culture, respectively. Our recent studies using the HFD model showed significant increases in IL-1β serum level that was mitigated by genetic deletion of TXNIP [26]. Together, these results highlight a potential role for circulating leukocytes in mediating EC death in models of HFD via both direct and indirect EC death pathways.…”
Section: Discussionmentioning
confidence: 71%
“…Fasting blood glucose levels were recorded at 8, 12 and 18 weeks, and HFD induced a modest yet significant increase in fasting blood glucose levels in WT-HFD when compared with the WT-ND group at 8 weeks through 18 weeks of study (* p < 0.05, n = 11-19, Table 1). TKO mice showed lower blood glucose levels and were partially protected against HFD-induced insulin resistance observed in WT-HFD mice as described before [26]. Table 1.…”
Section: Hfd Impact On Txnip Expression and Metabolic Profiles In Wt mentioning
confidence: 62%
See 1 more Smart Citation